The subgenus Empidideicus (Anomaloptilus) (Diptera: Mythicomyiidae) in Madagascar - Evenhuis, Neal L.; Gharali, Babak (Zootaxa, 2022)
The relatively uncommonly encountered subgenus Empidideicus (Anomaloptilus) is shown to be fairly diverse in Madagascar with eight known species. The subgenus is concentrated primarily in Southern Africa and Madagascar, ranges eastward through Arabia to Kazakhstan, and has a small disjunct population in the Canary Islands. Previous to this study, only one species was known from Madagascar (E. rhinoclypeatus Evenhuis). Including those described in this study, 18 species are now known in the subgenus worldwide, eight endemic to Madagascar, seven of which are herein described as new: E. (A.) andriambahomananii, n. sp., E. (A.) contrasticus, n. sp., E. (A.) hauseri, n. sp., E. (A.) irwini, n. sp., E. (A.) nanus, n. sp., E. (A.) regius, n. sp., and E. (A.) rinhai, n. sp. A key to the subgenera of Empidideicus and also to the species of the subgenus Anomaloptilus in Madagascar is given.